Comparison of activities of daily living impairments in Parkinson's disease patients as defined by the Pill Questionnaire and assessments by neurologists. Issue 9 (11th November 2013) - Lee, Wei-Ju; Chang, Yung-Yee; Lin, Juei-Jueng; Sung, Yueh-Feng; Li, Jie-Yuan; Wang, Shuu-Jiun; Chen, Rou-Shayn; Yang, Yuan-Han; Hu, Chaur-Jong; Tsai, Chon-Haw; Wang, Han-Cheng; Wu, Shey-Lin; et al.
Abstract : Objectives: To compare the clinical judgment of experienced neurologists after interviewing Parkinson's disease (PD) patients and their caregivers with the use of the Pill Questionnaire to determine the presence of impairments on activities of daily living (ADL). Background: ADL impairment is a criterion for the diagnosis of dementia associated with PD. The Pill Questionnaire has been recommended as a screening tool to assess ADL impairment in PD patients, but its usefulness and validity have not been fully investigated. Methods: We recruited idiopathic PD patients from 12 hospitals in Taiwan, and the patients underwent clinical assessments, a neuropsychological test battery and the Unified Parkinson Disease Rating Scale evaluation. The Pill Questionnaire was administered by study assistants. Patient and caregiver interviews were performed by experienced neurologists who were blinded to the Pill Questionnaire results. Results: In total, 284 PD patients (mean age 71.8±9 years, mean education 8.7±5.3 years, mean disease duration 5.4±5.3 years) were recruited. 63 patients showed ADL impairment by the Pill Questionnaire, and 108 patients showed ADL impairment by neurologists' clinical interviews. κ Statistics showed moderate agreement between the two methods (κ=0.521, p<0.001). Of the 108 patients who were diagnosed with ADL impairment by neurologists, only 56 patients (51.9%) showed impairment according to the Pill Questionnaire. Most of the missed patients had milder cognitive impairment and lower motor disability. Conclusions: A comprehensive interview is essential to determine the presence of ADL impairment in PD patients, especially in patients with early PD.